2015
DOI: 10.1186/s40693-015-0047-1
|View full text |Cite
|
Sign up to set email alerts
|

The presence of the marsupial Dromiciops gliroides in Parque Nacional Los Alerces, Chubut, Southern Argentina, after the synchronous maturation and flowering of native bamboo and subsequent rodent irruption

Abstract: Background: Dromiciops gliroides is a small nocturnal marsupial found in the temperate forests of Southern Chile and Argentina. It is the only living member of the order Microbiotheria. Here, we describe the discovery and first account of live trapping of D. gliroides in Parque Nacional Los Alerces (Los Alerces National Park) in the province of Chubut, Argentina. This account extends the distribution of this cryptic species south to Parque Nacional Los Alerces (PNLA). The study provides a description of the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
13
0
4
Order By: Relevance
“…2). The current distribution area of D. gliroides is based on 20 locations (Patterson et al 2003), but in more recent reports, Martin (2010) of and (Gurovich et al 2015) provided 69 additional occurrence locations, which fall within NatureServe's distribution map (except for one location at the north). Our study provides six new points, from which three are located southwards of the known distribution.…”
mentioning
confidence: 99%
“…2). The current distribution area of D. gliroides is based on 20 locations (Patterson et al 2003), but in more recent reports, Martin (2010) of and (Gurovich et al 2015) provided 69 additional occurrence locations, which fall within NatureServe's distribution map (except for one location at the north). Our study provides six new points, from which three are located southwards of the known distribution.…”
mentioning
confidence: 99%
“…We believe this is a unique and important study in Patagonia because it was carried out right after a "ratada," which has only been known to occur every 60-70 years or so [29,30] after massive flowering of native bamboo. It is necessary for urban students and their families to be more conscious about what happens during and after a rodent epidemic and how to decrease the chance of being infected by the devastating hantavirus, and students can be disseminators of this information.…”
Section: Laboratory Experience and Presenting Results To The Communitymentioning
confidence: 99%
“…In north-western Chubut province, massive flowering of the native bamboo Chusquea culeou occurred in late 2012 to early 2013 in Los Alerces National Park (LANP), 50 km from Esquel city [29]. This has been the first massive flowering and seeding event for the native bamboo in LANP in over 70 years [30].…”
Section: Mapuche Ethnobiological Heritage About Owlsmentioning
confidence: 99%
“…The sex of the pouch young could not be determined using criteria by Frankham & Temple-Smith (2012) and Gurovich et al (2013) because they are very small in size and newly born. Similarly, Tyndale-Biscoe & Renfree (1987) observed that it was impossible to determine the sex in the tammar wallaby and Virginia opossum (D. virginiana) at birth externally and only possible histologically.…”
Section: Age and Sex Estimatesmentioning
confidence: 99%
“…In this study, we also observe external oral morphology of newborn pouch young from the only living microbiotherian marsupial monito del monte (Dromiciops gliroides). Currently there is very little information on the morphology of microbiotherian pouch young (Muñoz-Pedreros et al 2005;Frankham & Temple-Smith, 2012;Gurovich et al 2013), this study will also bring together current knowledge and add new information on the only living member of the Microbiotheria (but see D'El ıa et al 2016 and below), a small arboreal marsupial that lives in the Andean valdivian forests of southern Chile and Argentina (Lobos et al 2005;Amico & Rodr ıguez-Cabal, 2009;Celis-Diez et al 2012;Gurovich et al 2015). It has only recently been proposed that two new different species of monito del monte exist, with one of the new species being endemic to Chile, and the other new species occurring in Argentina and Chile (D'El ıa et al 2016).…”
Section: Introductionmentioning
confidence: 99%